2014
DOI: 10.12811/kshsm.2014.8.1.051
|View full text |Cite
|
Sign up to set email alerts
|

The Related Factors with Improvement of Long-term Care Need of Residents and Quality of Service in Long-term Care Facility

Abstract: The purpose of this study was to investigate the relationship among staffing, occupancy rate, upward level change of long-term care need, and evaluation grade of facility. Data were obtained from National

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…This study also reported that the high turnover in RN staffing results in fewer hospitalizations. However, considering the specific staffing conditions in Korea-that CNAs can replace RNs, and visiting doctors only visit NHs once per month-having well-timed medical and nursing care in hospitals is very important to avoid prompt deterioration of health-related problems like pneumonia or infections of NH residents [17]. The interpretation should be performed cautiously for hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study also reported that the high turnover in RN staffing results in fewer hospitalizations. However, considering the specific staffing conditions in Korea-that CNAs can replace RNs, and visiting doctors only visit NHs once per month-having well-timed medical and nursing care in hospitals is very important to avoid prompt deterioration of health-related problems like pneumonia or infections of NH residents [17]. The interpretation should be performed cautiously for hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Most NHs are located in specific administrative districts, whereas some districts have a very limited number of NHs [4]. Most NHs (77.4%) are located in metropolitan and medium-sized cities, with the remainder in rural and fishing villages in Korea [17]. Consequently, competition among NHs varies widely by location.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…이에 따라 요양시설에서 입소 노인에게 제공하는 양질의 서비스 제공에 대한 요구와 관심이 늘어나고 있다 4,5) . 더불어 노인요양시설의 입소 노인 의 구강건강과 관련된 서비스 제공의 필요성을 주장하는 연 구가 많아지고 있다 6,7) .…”
unclassified